Digital Literacy Analysis of Middle School Students in Bogor Regency, West Java, Indonesia - Maria Cleopatra (PT FORMOSA CENDEKIA GLOBAL, 2022)
Digital literacy played an important role in human life now and in the future. This study aimed to describe and analyze the digital literacy of junior high school students in Bogor district. The number of respondents was 76 students from 2 junior high schools in Bogor district, West Java. The method used is a quantitative descriptive method. The results of the study prove that the intensity of implementing the use of digital literacy in learning activities and variations of digital-based reading materials and teaching aids is 73.2%, the remaining 22.8% do not yet have sufficient digital literacy. Based on the scores above, it can be said that digital literacy in the 2 schools is quite good. Schools are expected to increase digital use gradually, balanced with tiered training for students and teachers as well as staff employees in the school environment